Penggunaan Social Network Analysis Untuk Mencari Calon Pemimpin (Studi Kasus pada STIKOM Uyelindo Kupang) - Bulan, Semlinda Juszandri (Jurnal Teknologi Terpadu, 2020)
Many factors determine the success of an organization; one of the main factors is leadership. Leaders play a critical role in the success of an organization. This study aims to find potential leaders in STIKOM Uyelindo Kupang. In this study, the sample used was 53 people. Data were collected by distributing questionnaires to all staff at STIKOM Uyelindo Kupang. The method used to analyze data is Social Network Analysis (SNA); SNA can be used to study social relationships or interactions between members of an individual group. The software used to analyze social networks is NodeXL. The study results show that the nodes V15, V7, and V25 have the highest in-degree calculations, so it can be concluded that the three actors are potential future leaders. Â